Quality of Service and Community Disciplinary Officer with Quality Products for Variable Interviening Customer Satisfaction: National Savings Bank Syariah Branch Bogor Regency Cigombong - Marlapa, Eri (International Review of Management and Marketing, 2020)
Quality is the design is a function of product specifications, namely conformance in a measure of how far a product meets the requirements or quality specifications that have been determined from the totality of facilities and characteristics of products or services that meet the needs, express or implied. Product quality goals are difficult to understand because the expectations of consumers will always change. Every new standard is found, then consumers will demand more to get another new standard that is newer and better. In this view, quality is a process and not an end result (improving the quality of continuity). The study was conducted on customers of the National Sharia Savings Bank Branch of Cigombong, Bogor Regency. This research uses quantitative research. The populations in this study were customers who came to the Bogor branch of Cigombong Syariah Bank who used the services and facilities of a bank with a decent-sized sample in this study between 30 and 500. The researchers determined the number of samples taken for this study was 100 customers according to this opinion. The validity and reliability of the data uses the Pearson and Cronbach's Alpha product moment correlation formula. Keywords: Quality of Service, Discipline, Quality Products, Customer Satisfaction JEL Classification: M1 DOI: https://doi.org/10.32479/irmm.9946